Inventarisasi Reptil (Ordo Squamata) Pada Blok Pemanfaatan Di Taman Wisata Alam Sorong Distrik Klaurung Kota Sorong - yetty serkadifat; Lanny Wattimena; Falentinus Ngara (Universitas Muhammadiyah Sorong, 2026)
The Sorong Nature Tourism Park (TWA) area has the potential for high flora and fauna diversity so that the ecosystem condition is still relatively good and plays an important role as a habitat for various types of wildlife, including reptiles. This study aims to inventory the types of reptiles found in the Sorong Nature Tourism Park area, especially in the utilization block. The study was conducted in a sample area of ​​2 hectares through field observations and species identification based on morphological characters. The inventory results show that the area has quite good reptile diversity with the discovery of nine species belonging to two orders, namely Squamata and Testudines. The eight species from the Squamata order include the ground boa (Candoia aspera), the Pacific blue-tailed lizard (Emoia caeruleocauda), the curved-toed lizard (Cyrtodactylus marmoratus), the four-toed brown lizard (Carlia fusca), the blue-tongued lizard (Tiliqua gigas), the ground snake (Xenopeltis unicolor), the green python (Morelia viridis), and the tree boa (Candoia carinata). Meanwhile, one species from the order Testudines was discovered, the New Guinea short-necked turtle (Elseya novaeguineae). The nine species belong to four families: Boidae, Scincidae, Gekkonidae, and Chelidae. The results of this study indicate that the Sorong Nature Tourism Park area still has a relatively good level of reptile diversity, which requires continued protection through sustainable habitat management and conservation efforts. Keywords: inventory, reptiles (order Squamata)